Wag the Dog A Study on Film and Reality in the Digital Age - Thanouli, Eleftheria (Bloomsbury Academic, 2013)
Wag the Dog became a media event and a cultural icon because it inadvertently short-circuited the distance that is supposed to separate reality and fiction. The examination of the historical and social context in which it was produced, exhibited and received worldwide enables the author to illuminate a series of changes in the way a fiction film reflects and interacts with reality, urging us to reconsider some of our central and long-standing concepts or even paradigms in film theory. Eleftheria Thanouli provides new insights into a series of issues from both classical and contemporary film theory, such as the conceptual and ontological stakes in the use of digital technology, the impact of mass media on public memory and the political role of cinema in a globalized and conglomerated world.
Description based on print version record.
KU Select 2017: Backlist Collection
Keywords: Performing Arts / Film / History & Criticism; Performing arts; Electronic books